Assessment of Enteral Use of Perfluorane in Patients with Generalized Peritonitis - A. N. Belogrivtsev; R. D. Mustafin; I. Z. Kitiashvili; Yu. V. Kuchin (Общая реаниматология, 2009)
Objective: to analyze on basis of an integrative (clinical, biochemical, and microbiological) assessment, the efficiency of using perfluorane as a complementary component to correct the intestinal status in patients with peritonitis. Subjects and methods. The study was conducted in 106 patients with generalized peritonitis, who were comparable in the severity and degree of endotoxicosis. According to the treatment option, three study groups were arbitrarily formed: Group 1 that comprised 42 patients receiving complex intensive therapy (a clinical comparison group) and two major groups who underwent enterosorption during intensive therapy: Group 2 that included 26 patients in whom perfluorane was additionally injected interintestinally and Group 3 that consisted of 30 patients who did not take perfluorane. To evaluate the effect of injected perfluorane, the parameters of endotoxicosis were studied on days 1, 3, and 5 and the nasointestinal discharge was examined using the conventional procedure on days 1, 2, 3, and 4. The clinical picture of the disease was monitored in the early postoperative period. Results. The study has demonstrated a reduction in the parameters of endotoxicosis, as well as earlier recovery of motor evacuatory function and stabilization of enteric microbiocenosis. Conclusion. The intraintestinal use of perfluorane favored a better postoperative period and reduced lengths of hospital stay. Key words: peritonitis, intestinal failure, enterosorption, perfluorane.